Return to Sport After Bone–Patellar Tendon–Bone Autograft ACL Reconstruction in High School–Aged Athletes. Issue 6 (24th June 2021) - Rauck, Ryan C.; Apostolakos, John M.; Nwachukwu, Benedict U.; Schneider, Brandon L.; Williams, Riley J.; Dines, Joshua S.; Altchek, David W.; ,; Pearle, Andrew; Allen, Answorth; Stein, Beth Shubin; Dines, David; et al.
Background: Anterior cruciate ligament (ACL) injuries are occurring with increasing frequency in the adolescent population. Outcomes after ACL reconstruction (ACLR) are inconsistently reported in homogeneous patient populations. Purpose/Hypothesis: To evaluate outcomes after bone–patellar tendon–bone (BTB) autograft ACLR in competitive high school–aged athletes by examining return to sport (RTS), patient satisfaction, and reinjury rates. Our hypothesis was that RTS rates and satisfaction will be high and reinjury rates will be low. Study Design: Case series; Level of evidence, 4. Methods: An institutional ACL registry was utilized to identify competitive high school–aged athletes (14-18 years old) who underwent primary ACLR using BTB autograft with a minimum 2-year follow-up. A postoperative questionnaire was administered to determine rates and types of RTS, quality of sports performance, reinjury, and satisfaction. Uni- and multivariable analyses were used to identify demographic, sport-specific, and clinical factors related to RTS. Results: A total of 53 patients were included (mean ± SD age at the time of surgery, 16.6 ± 1.34 years). Mean follow-up was 3.78 ± 0.70 years (range, 2.60-4.94 years). The overall ipsilateral ACL retear rate was 7.5% (n = 4). There were 10 subsequent ACL tears to the contralateral knee (19%). Forty-four (83%) patients successfully returned to at least their prior level of sport at a mean 10.5 ± 8.7 months (range, 3-48 months). Overall satisfaction was high, with 91% of patients very satisfied with the outcome. Higher confidence levels regarding performance of the reconstructed knee were associated with increased probability of RTS on multivariate analysis. Conclusion: BTB autograft ACLR results in high rates of RTS and satisfaction and low rates of subsequent ipsilateral ACL injuries in competitive high school–aged athletes. Patients with higher confidence in performance of the reconstructed knee are more likely to return to at least their prior level of sport.